MEMBEDAH TEORI SOSIOLOGI: TEORI PERTUKARAN (EXCHANGE THEORY) GEORGE CASPAR HOMANS - Wardani, Wardani (Jurnal Studia Insania, 2016)
This article is aimed at analyzing critically George Caspar Homans?s theory of exchange. The critical analysis that may be called here simply as ?maping ideology? embodied in theory is needed to place the theory within the specific social and political condition, intellectual background, school of thought having great influence on it, and so forth, and also to assesses its limitedness as a theoretical frame-work of scientific research to explain complicated social phenomenon or human interaction. Influenced by psychological and economic theories, Homans?s theory of exchange has been intended at the beginning by the author as attack against Marxism domination that addressed criticism to capitalism as macro-structure oppressing the proletariat by the ruling class and against Durkheimian structural functionalism. By addressing the attack against Marxism and because of his intellectual and social background, Homans?s theory then has been regarded as an explanation justifying the existing situation. Being attributed as psychological reductionism, as neglecting the important role of structure, and deterministic are some of the objections addressed to his theory.